Communication reactions to the situation of provocation of jealousy in same-sex and opposite-sex friendship: a comparative analysis - Fourmanov, Igor A. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
The article discusses the results of an empirical study of differences in communication reactions to the situation of provocation of jealousy in same-sex and opposite-sex friendships. It is noted, that regardless of the type of friendship, the dominant strategies for both men and women are integrative communication, negative affective expression, and compensation (restoration). In men in same-sex friendships, communicative reactions to the situation of provocation of jealousy such as active distancing, avoidance (denial), distributive communication, control (restriction), compensation (substitution), and manipulation are less pronounced than in opposite-sex friendships. For women in same-sex friendships, compared to opposite-sex friendships, communicative reactions to the situation of provocation of jealousy such as active distancing and compensation (substitution) are more typical, but contact with the rival is less common. Four patterns of communication reactions to the situation of provocation of jealousy are identified and described: 1) destructive pattern; 2) constructive pattern; 3) avoidance pattern; 4) servility pattern.